Quinoline‐Derived Two‐Photon Sensitive Quadrupolar Probes. Issue 8 (3rd January 2017) - Tran, Christine; Berqouch, Nawel; Dhimane, Hamid; Clermont, Guillaume; Blanchard‐Desce, Mireille; Ogden, David; Dalko, Peter I.
Abstract: Quadrupolar probes derived from 8‐dimethylamino‐quinoline (8‐DMAQ) having a pegylated fluorene core were prepared and studied under "one‐photon" ( λ =365 nm) and "two‐photon" (TP) ( λ =730 nm) irradiation conditions. Compound1 a was identified as the most efficient probe by UV activation that showed sequential release of acetic acid as a model. Although the probe showed high two‐photon absorption it stayed inert under femtosecond irradiation conditions. Fast and selective photolysis was observed, however, by using picosecond irradiation conditions with a remarkably high TP uncaging cross‐section ( δ u =2.3 GM). Abstract : Light‐sensitive probes, derived from quinoline and pegylated fluorene, show high linear and two‐photon absorption values, fast fragmentation by λ =366 nm irradiation, and large two‐photon photolysis cross‐sections when excited with 1 ps pulses.